Structural Change in Relative Clauses and the Autonomy of Heritage Grammars - Frasson, Alberto (Languages (Basel), 2022)
This paper addresses the question of structural change in relative clauses in heritage speakers of two varieties of Venetan, a northern Italo-Romance language. It will be shown that appositive and restrictive relative clauses are not structurally distinguished in Brazilian Venetan, while they display different structural properties in Italian Venetan. It will be proposed that the phenomenon described in the paper does not depend on transfer from another language and it is not exclusively a matter of processing. The approach presented here aims to account for structural change in syntactic terms, without resorting to extra-linguistic factors. Heritage grammars are autonomous systems and follow predictable paths of language variation, as such, variation may take place at an interface level and at a syntactic level alike. This does not exclude possible influences from the dominant language, which, however, do not need to be taken as the only triggers of change.